RELASI SOSIAL EKONOMI DENGAN PARTISIPASI MASYARAKAT (kasus PHBM Perhutani di desa Donorejo, KPH Kedu Selatan) - , Triwahyudi Martanto, Prof. Dr. Ir. San Afri Awang, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Conditions of poverty and the participation of forest communities still remains a major concern in forestry development in Indonesia. Forest management in Java is held by Perhutani office also followed by the number of poor people who live around the state forest. Through Collaboration Forest Management System with Community (Pengelolaan Hutan Bersama Masyarakat = PHBM), Perhutani trying to improve the welfare of communities around the forest. This study aims to obtain data and information about the socio-economic conditions and participation of PHBM and seek explanations socio-economic relations with the community participation of PHBM participants in Donorejo village, district of Purworejo. This study was used a survey method with random sampling techniques. The collection of data through observation, interviews and documentation. Socioeconomic study is approached with an income per capita, expenditure per capita, land area owned, PHBM land area, ownership of livestock, poverty and the Gini Ratio (GR) stratification. Socio-economic relations with the participation calculated by non parametric statistical tests spearman rank correlation. Results showed that income per capita per year to reach Rp. 1,744,334 and expenditure per capita per year is Rp. 1,787,862. GR reveneu, expenditure, tenure, ownership of cattle, plantation, forestry, farms and fertilizer are at a low level of inequality. Activities of the agriculture business and labor has a value above 0.3 GR namely 0.36 and 0.37 are included in the moderate inequality. The score of community participation of PHBM participant is 1038 (moderate category). For the relation between socio-economic participation by spearman rank correlation test result spearman correlation coefficient (rs) as follows: income (0.74), expenditure (0.72), ownership of livestock (0.74) and PHBM area (0.54). Can be concluded that, the higher the income, expenditure, ownership of livestock and PHBM land holdings, the higher participation and have a strong relationship. For the vast holdings of land itself does not significantly associated with participation characterized by the value of rs = 0.37.